How many pathways for invasion of the red blood cell by the malaria parasite? - Pasvol, Geoffrey (Trends in parasitology, 2003)
Merozoites of the malaria parasite Plasmodium falciparum use several receptors for cellular engagement when they invade human red blood cells. Recently, a merozoite erythrocyte-binding protein, EBA-140, has been identified that specifically binds to glycophorin C on red blood cells. Up to 50% of Melanesians have a deletion in this gene, and the resultant Gerbich-negative red blood cells are relatively resistant to invasion. While discovery of multiple pathways for invasion could confound the search for suitable vaccine targets, they could also be considered in the design of therapeutic interventions that prevent malaria parasites entering red blood cells.